(untitled) (MAUSAM, 1979)
In this paper an attempt as been made to evaluate the capability of University of Virginia’s mesoscale(Plelke) model for air quality studies. The development of the physical equations and numerical techniques employee in model are described and deficiencies indicated. It is demonstrated that, although the Pielke model has certain limitation for air quality purposes, it can still provide valuable qualitative understanding of ambient air quality for a limited range of conditions.